The Impact of Gamification on Female Gen Z Users’ Continuance Intention to Use Digital Payment Method in Jakarta - Audrey Thalia Jesslyn; Chiquita Adaora; Jerry S. Justianto; Irene Bunga Amanda (International Journal of Social Service and Research (IJSSR), 2023)
The rapid advancement in technology today has altered the way and conduct of customers when making purchases. Almost every part of life has started to change from conventional to digital. This is relevant, for example, in the case of payment transactions. The large number of e-commerce industries, online transportation, and payment systems through digital payment applications reflect Indonesia's rapid digitalization. The payment system emerged as a revolution that transformed the cash payment system into a non-cash payment system. GoPay, OVO, Dana, Linkaja, Qris, Shopee Pay Later, Doku, and other digital payment methods are currently available in Indonesia. The aim of this study was to examine the impact of the gamification on the intention to continue using the Digital Payment Services. This form of study is known as quantitative analysis. This study's data source is primary data collected from digital payment users in Indonesia.